The Incidence of Torus Mandibularis in Malay Peoples - A. W. Jones (Dental Anthropology Association, 1996)
The incidence of torus mandibularlis is known to vary in world groups. The object os this study was to determine the incidence of torus mandibularis in Malay peoples. Comparison of the data with the known incidence is other world groups showed that the incidence of this trait in Malay people is not unusally high.